Out-of-pocket expenditure on chronic non-communicable diseases in Sub-Saharan Africa: the case of rural Malawi - Wang, Qun; Fu, Alex Z.; Brenner, Stephan; Kalmus, Olivier; Banda, Hastings Thomas; De Allegri, Manuela (PLOS ONE, 2015)
In Sub-Saharan Africa (SSA) the disease burden of chronic non-communicable diseases (CNCDs) is rising considerably. Given weaknesses in existing financial arrangements across SSA, expenditure on CNCDs is often borne directly by patients through out-of-pocket (OOP) payments. This study explored patterns and determinants of OOP expenditure on CNCDs in Malawi. We used data from the first round of a longitudinal household health survey conducted in 2012 on a sample of 1199 households in three rural districts in Malawi. We used a two-part model to analyze determinants of OOP expenditure on CNCDs. 475 respondents reported at least one CNCD. More than 60% of the 298 individuals who reported seeking care incurred OOP expenditure. The amount of OOP expenditure on CNCDs comprised 22% of their monthly per capita household expenditure. The poorer the household, the higher proportion of their monthly per capita household expenditure was spent on CNCDs. Higher severity of disease was significantly associated with an increased likelihood of incurring OOP expenditure. Use of formal care was negatively associated with the possibility of incurring OOP expenditure. The following factors were positively associated with the amount of OOP expenditure: being female, Alomwe and household head, longer duration of disease, CNCDs targeted through active screening programs, higher socio-economic status, household head being literate, using formal care, and fewer household members living with a CNCD within a household. Our study showed that, in spite of a context where care for CNCDs should in principle be available free of charge at point of use, OOP payments impose a considerable financial burden on rural households, especially among the poorest. This suggests the existence of important gaps in financial protection in the current coverage policy.
Gesehen am 29.06.2020